CORRELATION BETWEEN FARMER'S RESPIRATORY HEALTH AND INDOOR AIR QUALITY IN PULOKERTO AND SUNGAI REBO WETLAND AREA - Beby Yohaningsih; Tan Malaka; Novrikasari Novrikasari (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Wetland areas have humid temperatures and residential development will have a major effect on the air quality in the room which becomes humid and humid room air can cause several symptoms of respiratory disorders caused by airborne. This research was conducted in 35 farmer's houses which aims to determine the relationship between the respiratory health of farmers with air quality in the farmhouse and obtained results that are not related to the respiratory health of farmers with air quality in the room, where P>0.05 and there is one house that has good quality. high physical conditions such as humid temperatures and high chemical quality of the air due to storing tools and plowing fields at home with a fairly high number of bacteria and fungi.